EMOSI DAN PERILAKU MAKAN HUBUNGANNYA DENGAN KEJADIAN BERAT BADAN LEBIH PADA PNS DI KOTA TERNATE - , Sitti Salmiyah A. Bahruddin ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: The magnitude of overweight and obesity problems have been acknowledged as a global health problem by WHO. Psychological problems associated with overweight are emotion and eating behavior. According to data of Basic Health Research 2010, civil servants are a group susceptible to the problem of overweight. Objective: To identify association between emotion and eating behavior and the incidence of overweight in civil servants at Ternate Municipality. Method: The study was observational with case control design involving 106 civil servants at Ternate Municipality comprising 53 cases and 53 controls. Emotion was assessed using questionnaire of Emotional Eating Scale (EES), assessment of eating behavior based on Dutch Eating Behavior Questionnaire and intake was assesses using Semi Quantitative Food Frequency Questionnaire. Data analysis was using chi square and logistic regression. Result: All three parameters of EES had no correlation with the incidence of overweight in civil servants (p>0.05). Only one of three parameters of eating behavior had significant correlation with weight increase in civil servants, i.e. restrained behavior (OR=15.5). There was significant correlation between emotional eating and eating behavior restrained. There was significant correlation between eating behavior and calorie intake with OR of each parameter was 6.8 for restrained, 2.7 for emotion, and 4.8 for external. The result of double logistic regression analysis showed that factors significantly correlated with weight increase were restrained eating behavior and calorie intake. Conclusion: There was a significant association between Restrained eating behavior and calorie intake with the incidence of overweight. But no relationship was found between emotional and the incidence of overweight.